Association of Leukocyte Telomere Length With Perceived Physical Fatigability. (17th December 2021) - Zmuda, Joseph; Lee, Joseph; Honig, Lawrence; Christensen, Kaare; Feitosa, Mary; Wojczynski, Mary; Glynn, Nancy W; Katz, Ryan
Abstract: Leukocyte telomere length (LTL) is a potential marker of biological aging, but its relationship to fatigability, a prognostic indicator of phenotypic aging (e.g., functional decline) is unknown. We hypothesized shorter LTL would predict greater perceived physical fatigability. Two generations of participants (N=1, 997; 309 probands, 1, 688 offspring) were from the Long Life Family Study (age=73.7±10.4, range 60-108, 54.4% women). LTL was assayed at baseline and 8.0±1.1 years later perceived physical fatigability was measured using the validated, self-administered 10-item Pittsburgh Fatigability Scale (PFS, 0-50, higher scores=greater fatigability). Prevalence of greater physical fatigability (PFS scores≥15) was 41.9%. Using multivariate linear regression, one kilobase pair shorter LTL predicted higher PFS Physical scores (β=0.9, p=0.025), adjusted for family relatedness, generation (indicator for age), field center, follow-up time, sex, and follow-up body mass index, physical activity, health conditions. LTL, a promising marker of future fatigability, may allow for early identification of those at-risk for deleterious aging.